2019
DOI: 10.3727/096504018x15446984186056
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Induces Epithelial‐Mesenchymal Transition in Nasopharyngeal Carcinoma Cells Through Activation of the PI3K/AKT Pathway

Abstract: Nasopharyngeal cancer (NPC) is a malignant epithelial carcinoma of the head and neck. Cancer therapy targeting programmed cell death protein-1 (PD-1) or programmed death ligand-1 (PD-L1) is revolutionary. However, the tumorigenic mechanism of PD-L1 is not yet clear in NPC. Here we demonstrated an oncogenic role of PD-L1 via activating PI3K/AKT in NPC cells. PD-L1 overexpression was frequently detected in NPC biopsies and cell lines by qRT-PCR. PD-L1 overexpression and knockdown demonstrated that PD-L1 promoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…6a). Numerous studies have reported that the PI3K/AKT pathway plays an important role in metastasis through the regulation of EMT [23][24][25]. Therefore, the PI3K inhibitor LY294002 [26][27][28][29] was used to detect the effect of the PI3K/AKT pathway on AGK-induced RCC proliferation and metastasis.…”
Section: Agk Promotes Rcc Proliferation and Metastasis Via The Pi3k/amentioning
confidence: 99%
“…6a). Numerous studies have reported that the PI3K/AKT pathway plays an important role in metastasis through the regulation of EMT [23][24][25]. Therefore, the PI3K inhibitor LY294002 [26][27][28][29] was used to detect the effect of the PI3K/AKT pathway on AGK-induced RCC proliferation and metastasis.…”
Section: Agk Promotes Rcc Proliferation and Metastasis Via The Pi3k/amentioning
confidence: 99%
“…Similarly, synthetic peptides that either target PD-L1 degradation or post-translational modifications have shown a strong efficiency in animal studies, which may serve as a novel therapy for cancer treatment (351, 365). Notably, this kind of therapy that directly targets PD-L1 is of great significance and may be more effective as compared with blockade of PD-1/PD-L1 axis due to PD-1-independent functions of PD-L1 in the promotion of malignant phenotypes and drug resistance (367, 368). Altogether, an extensive understanding of the mechanisms by which PD-L1 is governed will help us to reach a comprehensive evaluation of PD-1/PD-L1 targeting therapy, and further potentiate the efficacy and expand the usage of this kind of cancer therapy via patient selection and rational combination with other antineoplastic agents, as well as develop new effective strategies for cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CD163 is considered the most speci c marker of TAMS, involved in the occurrence, development, migration, angiogenesis, EMT, etc., of GBM [42,43]. PD-L1 is the focus of current immunotherapy research, the study found that its expression is closely related to EMT [44,45], and EMT is the focus of current cancer resistance research [46,47]. But no research has been done to explore the causes of individualization of patient therapy through their relationship.…”
Section: Discussionmentioning
confidence: 99%